Poesía y colonialismo: Maia de Gabriele D’Annunzio - Abate, Sandro (Cuadernos de Filología Italiana, 2010)
Maia, the first of the Laudi volumes by Gabriele D’Annunzio, has been exalted by the critics from two perspectives: on account of its mythical and symbolic content (a journey back to the classical sources of western culture), and for its connection with F. Nietzsche’s philosophical ideas. In this paper we propose a new reading of the 1903 text, in which particular attention will be paid to aspects arising from developments brought about by post-colonial studies. Starting from several structural observations, there follows an analysis of the heroic model presented by the text in paralel with Ulyses and Boggiani, thus revealing the values assigned to the imperialist ideas of social darwinism and their subsequent position in a particular segment of the dominant culture.